1991
DOI: 10.1128/aac.35.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Differing activities of quinolones against ciprofloxacin-susceptible and ciprofloxacin-resistant, methicillin-resistant Staphylococcus aureus

Abstract: The in vitro activities of nine quinolones (seven fluoroquinolones, nalidixic acid, and acrosoxacin) against methicillin-resistant Staphylococcus aureus (MRSA) were compared with those of the glycopeptides teicoplanin and vancomycin. MICs against 160 strains of ciprofloxacin-susceptible (MIC, <2.0 ,ug/ml) MRSA and 40 strains of ciprofloxacin-resistant (MIC, .2.0 tig/ml) MRSA were determined. The following MICs for 50% of the strains tested (in micrograms per milliliter) were obtained for ciprofloxacin-suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Two strains (221 SCV and 927 SCV ) produced growth revertants (designated 221 REV and 927 REV ) at rates of 1.76 ϫ 10 Ϫ6 and 1.21 ϫ 10 Ϫ6 per cell per generation, respectively, as assessed by fluctuation analysis (22). These rates are consistent with expected values for the reversion of a point mutation and are similar to other data in the literature reported for reversion of SCV strains (26,27). Sanger DNA sequencing confirmed that the revertant strains had a wild-type allele of the cognate men gene.…”
Section: Isolation Of S Aureus Scvssupporting
confidence: 80%
“…Two strains (221 SCV and 927 SCV ) produced growth revertants (designated 221 REV and 927 REV ) at rates of 1.76 ϫ 10 Ϫ6 and 1.21 ϫ 10 Ϫ6 per cell per generation, respectively, as assessed by fluctuation analysis (22). These rates are consistent with expected values for the reversion of a point mutation and are similar to other data in the literature reported for reversion of SCV strains (26,27). Sanger DNA sequencing confirmed that the revertant strains had a wild-type allele of the cognate men gene.…”
Section: Isolation Of S Aureus Scvssupporting
confidence: 80%
“…This may just reflect the observation that the frequency of spontaneous mutation to quinolone resistance among initially quinolonesusceptible staphylococci is i0-7 to 10- (7,14,30), which is too low to have been observed with the 102 to 106 CFU used in our experiments. This does not mean, however, that a short course of perioperative treatment in humans will not select for quinolone-resistant staphylococci in niches harboring a more complex and numerous staphylococcal flora such as the nares or skin.…”
Section: Resultsmentioning
confidence: 49%
“…Cephalosporins appear to be ineffective in preventing infection by such pathogens. In contrast, the new fluoroquinolones exhibit in vitro activity against most common clean surgical wound pathogens, including many isolates of staphylococci and gram-negative species (4,15,30,43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These flasks, along with a control flask to which no test drug was added, were placed in a gyrating incubator at 37c. Quantitative bacterial counts after 0, 2, 4, 8, and 24 h of exposure to the agents were performed by spreading 0.1 ml of the appropriate dilutions onto Mueller-Hinton agar plates which were The mutation rate was considered to be the ratio of the number of the resistant colonies over the total microbial count (13). The 117 strains of S. sonnei studied showed diverse antibiograms and plasmid patterns, and there was no evidence of epidemiologic relatedness among the strains.…”
mentioning
confidence: 99%